Ectopic Gene Conversions in the Genome of Ten Hemiascomycete Yeast Species. (17th October 2010) - Morris, Robert T.; Drouin, Guy
Abstract : We characterized ectopic gene conversions in the genome of ten hemiascomycete yeast species. Of the ten species, three diverged prior to the whole genome duplication (WGD) event present in the yeast lineage and seven diverged after it. We analyzed gene conversions from three separate datasets: paralogs from the three pre-WGD species, paralogs from the seven post-WGD species, and common ohnologs from the seven post-WGD species. Gene conversions have similar lengths and frequency and occur between sequences having similar degrees of divergence, in paralogs from pre- and post-WGD species. However, the sequences of ohnologs are both more divergent and less frequently converted than those of paralogs. This likely reflects the fact that ohnologs are more often found on different chromosomes and are evolving under stronger selective pressures than paralogs. Our results also show that ectopic gene conversions tend to occur more frequently between closely linked genes. They also suggest that the mechanisms responsible for the loss of introns in S. cerevisiae are probably also involved in the gene 3 ' -end gene conversion bias observed between the paralogs of this species.